Highly Durable and Ultrafast Cycling of Dual‐Ion Batteries via In Situ Construction of Cathode–Electrolyte Interphase. Issue 44 (16th September 2022) - Cheng, Zhenjie; Guo, Longfei; Dong, Qingyu; Wang, Chunting; Yao, Qian; Gu, Xin; Yang, Jian; Qian, Yitai
Abstract: Dual‐ion batteries have shown promising prospect in energy storage, owing to their low material costs, high power capability, and environmental friendliness. However, graphite as the cathode always suffers from structural damage and electrode/electrolyte interface instability, which greatly deteriorate their electrochemical performance. Here, tris(trimethyl‐silyl) phosphite (TMSP) is added as an electrolyte additive to improve the electrochemical performance. TMSP not only scavenges the deleterious species generated by electrolytes, but also produces a thin and uniform cathode–electrolyte interphase layer on graphite. Hence, the electrochemical performance is greatly promoted. In graphite||graphite, the capacity retention is ≈96.8% at 30 °C or 92.5% after 3000 cycles in the presence of TMSP, much better than those without TMSP (62% at 30 °C or 27% after 200 cycles). Abstract : Here, tris(trimethylsilyl) phosphite (TMSP) is added as an electrolyte additive to improve the performance of dual‐ion batteries. TMSP not only scavenges the deleterious species generated by electrolytes, but also produces a thin and uniform cathode–electrolyte interphase layer on graphite. In graphite||graphite, the capacity retention is ≈96.8% at 30 °C or 92.5% after 3000 cycles in the presence of TMSP.